Role of curcumin in ischemia and reperfusion injury - Minglei Bi; Danyi Li; Jin Zhang (Frontiers Media S.A., 2023)
Ischemia-reperfusion injury (IRI) is an inevitable pathological process after organic transplantations. Although traditional treatments restore the blood supply of ischemic organs, the damage caused by IRI is always ignored. Therefore, the ideal and effective therapeutic strategy to mitigate IRI is warrented. Curcumin is a type of polyphenols, processing such properties as anti-oxidative stress, anti-inflammation and anti-apoptosis. However, although many researches have been confirmed that curcumin can exert great effects on the mitigation of IRI, there are still some controversies about its underlying mechanisms among these researches. Thus, this review is to summarize the protective role of curcumin against IRI as well as the controversies of current researches, so as to clarify its underlying mechanisms clearly and provide clinicians a novel idea of the therapy for IRI.